Enhancement of prostaglandin D2-D prostanoid 1 signaling reduces intestinal permeability by stimulating mucus secretion - Hayashi, Akane; Sakamoto, Naoaki; Kobayashi, Koji; Murata, Takahisa (Frontiers in Immunology, 2023)
The intestinal barrier plays a crucial role in distinguishing foods from toxins. Prostaglandin D2 (PGD2) is one of the lipid-derived autacoids synthesized from cell membranederived arachidonic acid. We previously reported that pharmacological stimulation of PGD2 receptor, D prostanoid 1 (DP1) attenuated the symptoms of azoxymethane/dextran sodium sulfateinduced colitis and ovalbumin-induced food allergy in mouse models. These observations suggested that DP1 stimulation protects the intestinal barrier. The present study aimed to uncover the effects of DP1 stimulation on intestinal barrier function and elucidate the underlying mechanisms. Materials and methods: Intestinal permeability was assessed in mice by measuring the transfer of orally administered fluorescein isothiocyanate-dextran (40 kDa) into the blood. The DP1 agonist BW245C (1 mg/kg) was administered 10 min prior to dextran administration. The intestinal permeability was confirmed using the ex vivo everted sac method. Tight junction integrity was evaluated in vitro by measuring the transepithelial electrical resistance (TER) in the human intestinal epithelial cell line Caco-2 in vitro. Mucus secretion was assessed by observing Alcian Blue-stained intestinal sections. Results: Pharmacological DP1 stimulation reduced intestinal permeability both in vivo and ex vivo. Immunohistochemical staining showed that DP1 was strongly expressed on the apical side of the epithelial cells. DP1 stimulation did not affect TER in vitro but induced mucus secretion from goblet cells. Mucus removal by the mucolytic agent N-acetyl-l-cysteine canceled the inhibition of intestinal permeability by DP1 stimulation. Conclusion: These observations suggest that pharmacological DP1 stimulation decreases intestinal permeability by stimulating mucus secretion.